Optimalisasi Pelaksanaan Inventarisasi Dan Pelaporan Barang Milik Daerah Dalam Rangka Pengelolaan Aset Tetap Pada BPKAD Kabupaten Blitar - Sari, Dita Natalia; Mutiara, Nisa; Askafi, Eka; Mulyaningtiyas, Ratna Dewi (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
The purpose of this research is to find out how the implementation and stages of inventorying and reporting of regional property, what are the obstacles encountered, and how to optimize the implementation of inventory and reporting of regional property at BPKAD Blitar Regency. This type of research is descriptive qualitative with interviews as the main tool for collecting data.In this study there were 6 keys informants and 3 supporting informants. The results of the study showed that the inventory and reporting of regional property was carried out in all OPDs in Blitar Regency and had been carried out in accordance with the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 47 of 2021 concerning Procedures for Carrying Out Bookkeeping, Inventory and Reporting of Regional Property, however it was still Obstacles were encountered, namely the lack of human resources and the administration of recording regional property in Blitar Regency was still not in order, so that the implementation of inventory and reporting of regional property could not be said to be optimal. The author suggests to conduct training for goods administrators.